2(5+7p)-3=7(4p-7)

Simple and best practice solution for 2(5+7p)-3=7(4p-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5+7p)-3=7(4p-7) equation:



2(5+7p)-3=7(4p-7)
We move all terms to the left:
2(5+7p)-3-(7(4p-7))=0
We add all the numbers together, and all the variables
2(7p+5)-(7(4p-7))-3=0
We multiply parentheses
14p-(7(4p-7))+10-3=0
We calculate terms in parentheses: -(7(4p-7)), so:
7(4p-7)
We multiply parentheses
28p-49
Back to the equation:
-(28p-49)
We add all the numbers together, and all the variables
14p-(28p-49)+7=0
We get rid of parentheses
14p-28p+49+7=0
We add all the numbers together, and all the variables
-14p+56=0
We move all terms containing p to the left, all other terms to the right
-14p=-56
p=-56/-14
p=+4

See similar equations:

| x+6+6x-58=180 | | 1.3-x+2.1=5.7 | | b-5.73=3.27 | | 2m-3)m+1)=4(m+3) | | 12​(x−​5)=11​(x+​5) | | 148=4(1-6n) | | x+5=(x–2)–(2x–7) | | 106-11x(11x)=0 | | 10(-5x+6)-9=1+5(-10x+10) | | 4-3x+8x-4-4x=12 | | 4(3x-11)=12x | | 4x+23+10x-1=24 | | 2x-3(x+2)=5 | | 3x(4x-40)=360 | | 3x-3-3=9 | | 36p=61 | | 49-3m=4m+14* | | 99.9x=24.9 | | 4-3x=8x-4-4x=12 | | 5x+x+4+3x+4=41 | | k+5/3=7/2 | | 5-(x-8)=2(x+10) | | -4=5x-17-22x | | 3(a-5)+9=-2 | | +6x+3=8-6x | | 2x+5=3+6× | | (6x+1)=23 | | 3/4x=44-2x | | 8x+4=-2-16 | | w3+7=9 | | 12x+1.2=–10.2 | | 2/3c=23 |

Equations solver categories